NUMERICAL COMPUTATION OF LAMINAR NATURAL CONVECTION IN TRIANGULAR SHAPED CAVITIES - Kent, Emin Fuad (WIT Transactions on Engineering Sciences, 2020)
In the present work, a numerical analysis of laminar natural convection in right and isosceles triangular enclosures has been carried out. Two dimensional, steady-state governing equations (conservation of mass, momentum and energy) were solved in Cartesian coordinates by the finite volume method. Several configurations are examined over a range of Rayleigh numbers that ranged from 103 to 105; for cavity walls that are heated, cooled or insulated. Streamlines and isotherms are displayed as streamline plots and isotherm lines for various triangular enclosures and, for Rayleigh number ranged from 103 to 105 with heated from the bottom. The effect of the aspect ratio, that is taken as a parameter, on the convective flow and isothermal contours in the triangular cavity are examined in detail. Symmetry breaking pitchfork bifurcations and multicellular flow structures and their effects on temperature distributions at low aspect ratios and high Rayleigh numbers are inspected. The overall heat transfer capabilities of the isosceles triangular enclosures are evaluated and assessed by examining the average convective Nusselt numbers.